Genetically encoded formaldehyde sensors inspired by a protein intra-helical crosslinking reaction - Rongfeng Zhu (Nature Portfolio, 2021)
In order to understand the role of formaldehyde in living systems, real-time monitoring is required. Here the authors report a genetically encoded, reaction-based formaldehyde sensor (FAsor) that enables visualisation of formaldehyde in mammalian cells and tissues.